Development of Artificial Diet and Optimum Feeding Strategy For Malaysian River Catfish Mystus Nemurus (Cuvier and Valenciennes) Larvae - Eguia, Ruel Villacorte (1998)
Four feeding experiments were conducted to evaluate the growth and survival of Mystus nemurus larvae under different diets and feeding regimes. First experiment evaluated the influence of the gradual and direct weaning techniques on growth and survival of the larvae. Newly hatched live food (Artemia nauplii) was provided to all treatments at the start of exogenous feeding. For gradual weaning scheme, the live food was gradually decreased on day 4 or 6 until the larvae were on 100% artificial diet. In contrast the larval diet was shifted from live food to 100% artificial diet starting day 6 or 10 for direct weaning scheme while the controls were fed on Artemia throughout the study. This study showed that gradual weaning at day 4 of exogenous feeding gave better growth and survival rate comparable to the controls and seemed to be the most economically and biologically viable techniques for feeding M. nemurus larvae. The second experiment was conducted to study the effect of feed particle size on feeding behavior and ultimately growth and survival of larvae. Different feed particle sizes were administered at different stages of weaning. In Treatment I, the larvae were given an assorted size «425-700µm) diet at the start of weaning onwards. Larvae on Treatment II were given different sizes of diet for different period. i.e. <425µm at the start of weaning (day 4) to day 8, 425-600µm from day 9 to day 12 and 600-700µm from day 13 to day 16. The two treatments were also tested without any weaning or live food while the control was similar to Experiment I. Treatment I gave the best growth and survival rate equivalent to the control. Continuos feeding of a wide range of feed particle size during larviculture seemed to benefit the uneven growth rate in M. nemurus larvae. Treatments without weaning gave inferior growth and total mortality after day 8.